A preliminary determination of the physico-chemical constants of dogfish shark-liver oil (Squalus Acanthias). - Penuela, Cynthia A (1985.)
This study determines the physico-chemical constants of spiny dogfish shark (S. acanthias) - liver oil processed in San Joaquin. The oil was analyzed for its moisture, refractive index, specific gravity, viscosity, saponification number, soluble acid, acid value, free fatty acid, ester value, acetyl value, iodine number and unsaponifiable matter., On the average, the physical constants obtained are: negligible amount of moisture, 0.8688 specific gravity, and a viscosity of 16.3711 centipoise. (p)The chemical constants are: saponification number, 266; soluble acid, 0.0132; acid value, 0.1143; free fatty acid, 0.0564 ; ester value, 266; acetyl value, 1.5186; iodine number, 140; and unsaponifiable matter, 30.
Thesis (Undergraduate, Bachelor of Science in Natural Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miag-ao, Iloilo.
Keywords: Oil -- Dogfish Shark-Liver.